Sequential therapy with topical clobetasol for 14 days followed by hydroquinone versus hydroquinone alone in facial melasma treatment: a randomized, double-blind, controlled clinical trial - de Amorim, Rebecca P. [UNESP] (2024)
Background: Clobetasol has demonstrated remarkable results in treating melasma within a short time frame; however, its use is limited because of the risk of local side effects. To date, there is no controlled trial on sequential clobetasol/hydroquinone for melasma. This study aimed to investigate the tolerability and efficacy of 0.05% clobetasol followed by 4% hydroquinone (CLOB-HQ) in comparison to the isolated use of 4% hydroquinone (HQ). Methods: A double-blinded, randomized clinical trial involving 50 women with facial melasma was performed. They were directed to apply 0.05% clobetasol every night for 14 days, followed by 4% hydroquinone for 46 days (CLOB-HQ group), or the use of hydroquinone for 60 days (HQ group). Evaluations were carried out at inclusion, and after 14 and 60 days of treatment, measuring modified Melasma Area and Severity Index (mMASI), Melasma Quality of Life scale (MELASQoL), and colorimetry. The Global Aesthetic Improvement Scale (GAIS) was assessed by a blinded evaluator. Results: There was no difference in the main outcomes at D14 and D60 (P > 0.1). For CLOB-HQ, the mean (CI 95%) reduction in mMASI was 13.2% (5.1–21.3%) and 43.1% (32.2–54.0%) at D14 and D60, and for HQ, they were 10.6% (5.9–27.5%) and 44.8% (33.2–52.3%). The MELASQoL, colorimetric luminosity, and GAIS showed a progressive improvement for both groups despite no difference between them. No severe side effects were identified. No cases of telangiectasias, atrophy, or perioral dermatitis were associated with the use of CLOB. Conclusion: The sequential CLOB-HQ regimen was safe and well tolerated, even though its efficacy was not different from HQ after 14 or 60 days of treatment. Based on these findings, the use of clobetasol 14 days before hydroquinone is not advisable for the treatment of melasma.